Pengaruh Pupuk Boron Cair Terhadap Karakteristik Morfologi dan Produktivitas Biomassa Sorgum Samurai 1 (Sorghum Bicolor (L) Moench): Effect Of Liquid Boron Fertilizer On Morphology Characteristics And Biomass Produktitivity Of Sorghum Samurai 1 (Sorghum Bicolor (L) Moench) - Romadhon, Achmad; Abdullah, Luki; Karti, Panca Dewi Manu Hara (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
This study aims to evaluate the effect of liquid boron fertilizer on the morphological characteristics and biomass productivity of sorghum samurai 1. The research design used a randomized block design (RBD) 5 x 8, resulting in 40 treatments. The factor applied was liquid boron fertilizer with the following variations: A0= no boric acid addition; A1 = boric acid 10 ppm (equivalent to 0.360 g H3BO3/5L); A2 = boric acid 20 ppm (equivalent to 0.720 g H3BO3/5L); A3 = boric acid 30 ppm (equivalent to 1.080 g H3BO3/5L); A4 = boric acid 40 ppm (equivalent to 1.440 g H3BO3/5L). The results showed that 20 to 30 ppm does significantly increased leaf length, plant height, and chlorophyll content (p<0.05). However, there was no significant effect on biomass production, nutrient evaluation, and fiber fractions. In conclusion, boron contributes to the vegetative growth of the plant but does not significantly affect biomass production, nutrient evaluation, and fiber fractions of sorghum samurai 1